Avian Test Battery for the Evaluation of Developmental Abnormalities of Neuro- and Reproductive Systems - Kawashima, Takaharu; Ahmed, Walaa M. S.; Nagino, Koki; Ubuka, Takayoshi; Tsutsui, Kazuyoshi (Frontiers in Neuroscience, 2016)
Most of the currently used toxicity assays for environmental chemicals use acute or chronic systemic or reproductive toxicity endpoints rather than neurobehavioral endpoints. In addition, the current standard approaches to assess reproductive toxicity are time-consuming. Therefore, with increasing numbers of chemicals being developed with potentially harmful neurobehavioral effects in higher vertebrates, including humans, more efficient means of assessing neuro- and reproductive toxicity are required. Here we discuss the use of a Galliformes-based avian test battery in which developmental toxicity is assessed by means of a combination of chemical exposure during early embryonic development using an embryo culture system followed by analyses after hatching of sociosexual behaviors such as aggression and mating and of visual memory via filial imprinting. This Galliformes-based avian test battery shows promise as a sophisticated means not only of assessing chemical toxicity in avian species but also of assessing the risks posed to higher vertebrates, including humans, which are markedly sensitive to nervous or neuroendocrine system dysfunction.